2020
DOI: 10.18002/rama.v15i2.6257
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between psychological resilience and stress coping strategies in karate athletes

Abstract: <p>The aim of this research was to examine the psychological resilience and stress coping strategies of Karate athletes according to some demographic variables and to determine the relationship between them. A sample of 104 (54 females and 50 males, mean age 19.85±4.10 years) Karate athletes who trained in different sport clubs in Turkey were recruited. The <em>Brief Resilience Scale (BRS)</em> (Smith et al., 2008) and the <em>Stress Coping Scale (SCS)</em> (Sahin &amp; Durak,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
2
3
0
Order By: Relevance
“…Group comparisons showed higher mental strength in the <2, 2-5, and >5 years of experience groups than the participants with no CS experience. These findings are congruent with the results found by Küçük (2020), who showed a significantly positive correlation between resilience and experience in karatekas. Pujszo et al (2019) found a significant positive relationship between CS experience and resilience in adult practitioners.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Group comparisons showed higher mental strength in the <2, 2-5, and >5 years of experience groups than the participants with no CS experience. These findings are congruent with the results found by Küçük (2020), who showed a significantly positive correlation between resilience and experience in karatekas. Pujszo et al (2019) found a significant positive relationship between CS experience and resilience in adult practitioners.…”
Section: Discussionsupporting
confidence: 92%
“…Hypothesis 4 was retained as the comparison between sexes revealed higher mental strength in males than females. This finding is congruent with the results of Küçük (2020), Pujszo et al (2019), andLorenco-Lima (2023), who also found psychological (resilience and grit) differences between male and female CS practitioners.…”
Section: Supporting Agenciessupporting
confidence: 90%
“…Psychological resilience is a factor in dealing with stress. The results of this research explain that a confident approach and an optimistic approach have a positive and medium correlation in reducing stress in karate athletes (Kuçuk Kiliç, 2020).…”
Section: Introductionmentioning
confidence: 66%
“…In the current research, martial artists registered a moderate level of resilience, a low level of Foul play, a slightly below average level for Go-ahead factor, and an average level of Assertiveness (at group level). In addition, specialized literature mentioned that martial arts athletes’ resilience (karate practitioners) was at mid-level ( Kuçuk Kiliç, 2020 ) (BRS was used). Considering assertiveness, it was found that male athletes in individual sports (including taekwondo, judo, and wrestling) registered high values; however, only 32% of athletes, in the entire sample, were martial artists ( Yetis, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the current research, McDonald’s ω reliability coefficient was 0.78. BRS was used in previous research on martial artists ( Kuçuk Kiliç, 2020 ).…”
Section: Methodsmentioning
confidence: 99%